Voluntary human capital disclosure and firm value relationship in the listed companies of Bangladesh: a conceptual overview / Shamem Ara Mili and Fathyah Hashim - Mili, Shamem Ara; Hashim, Fathyah (Universiti Teknologi MARA, 2020)
The aim of this paper is to incorporate relevant empirical researches and literature for extending the potentials of voluntary human capital disclosure to increase the value of the listed firms in Bangladesh. Voluntary human capital disclosure reduces information asymmetry and increases the financial lucidity of the business, and hence, could minimize agency conflicts, and satisfy employees' and other stakeholders' of the business. However, subsequent to a 13.8 percent drop in 2018, the broad index of the Dhaka Stock Exchange Limited lost 17.3 percent in 2019. It is among the first paper focusing on the consequence of voluntary human capital disclosures on firm value from a combination of agency theory, signaling theory, and stakeholder theory perspective. Moreover, extant literature endow with inconsistent and less evidence concerning the relationship of voluntary human capital disclosure with firm value. The present paper proposes and illustrates potential proposition for future empirical investigation in the context of an emerging economy like Bangladesh. It is also expected that the present paper would endow with further knowledge to investors, managers, and other stakeholders to upgrade firm value by means of voluntary human capital disclosure in their corporate reporting practices.